Molecular Docking, Molecular Dynamics Studies and ADMET Analysis of Resveratrol Interacting with BSA - Ben Thamer, Mohammed Salah Eddine.; Khezzane, Hicham.; Bouznada,Yousef . (University of Eloued جامعة الوادي, 2025)
Resveratrol is a naturally occurring polyphenol known for its wide-ranging therapeutic potential, including antioxidant, anti-inflammatory, and anticancer activities. However, its clinical application is limited by poor solubility and low bioavailability. This thesis investigates the binding interactions and pharmacokinetic behavior of trans- and cis-resveratrol isomers with Bovine Serum Albumin, a model transport protein, using an integrated in silico approach. Molecular docking was employed to predict the binding affinity and interaction modes of each isomer with BSA. Results revealed that trans-resveratrol exhibited stronger binding affinity and more favorable non-covalent interactions compared to the cis isomer. These findings were supported by molecular dynamics (MD) simulations over 100 picoseconds, which assessed structural parameters such as root mean square deviation (RMSD), root mean square fluctuation (RMSF), radius of gyration (Rg), solvent-accessible surface area (SASA), and hydrogen bonding patterns. The BSA–trans-resveratrol complex demonstrated greater conformational stability and compactness, whereas the cis isomer induced more flexibility and dynamic fluctuation. In addition, ADMET (Absorption, Distribution, Metabolism, Excretion, and Toxicity) analysis was conducted to evaluate the pharmacokinetic profiles of both isomers. Both forms showed favorable drug-likeness, high intestinal absorption, and low predicted toxicity. Notably, neither isomer was predicted to cross the blood–brain barrier or act as a P-glycoprotein substrate. Overall, this study highlights the superior binding stability and pharmacokinetic characteristics of trans-resveratrol, supporting its potential as a more effective candidate for albumin-mediated drug delivery. The findings provide a foundation for future formulation and development of resveratrol-الريسفيراترول هو متعدد فينولات طبيعي يُعرف بإمكاناته العلاجية الواسعة، بما في ذلك خصائصه المضادة للأكسدة، والمضادة للالتهابات، والمضادة للسرطان . ومع ذلك، فإن تطبيقه السريري محدود بسبب ضعف ذوبانيته وانخفاض توافره الحيوي . تبحث هذه الإشكالية في تفاعلات الارتباط والسلو ك الدوائي لمشتقات الريسفيراترول مع ألبومي ن مصل البقر (BSA) ، وهو بروتين ناقل وظيفي، باستخدام منه ج متكامل قائم على المحاكا ة الحاسوبية . تم استخدام الالتحام الجزيئي Docking) (Molecular للتنبؤ بألفة الارتباط وأنماط التفاعل لكل مشتق ريسفيراترول مع BSA . أظهرت النتائ ج أ ن إيزومر ترانس -ريسفيراترول يمتلك ألفية ارتباط أقوى وتفاعلات غير تساهمية أكثر ملاءمة مقارنة بإيزومر سيس . وقد دُعمت هذه النتائج بمحاكاة الديناميكا الجزيئية (MD) لمدة 100 بيكوثانية، حيث تم تقييم عدة معايير بنيوية مثل : الانحراف الجذري المتوسط (RMSD) ، التذبذب الجذري المتوسط (RMSF) ، نصف قطر الدوران (Rg) ، المساحة السطحية المتاحة للمذيب (SASA) ، وعدد الروابط الهيدروجينية . أظهر -BSA ترانس -ريسفيراترول ثباتًا بنيويًا أكبر وبنية أكثر إحكامًا، بينما تسبب إيزومر سيس في مرونة أعلى وتقلبات بنيوية أكبر . كما تم إجراء تحليل ADMET )الامتصاص، والتوزيع، والاستقلاب، والإطراح، والسمية ( لتقييم الملف الدوائي لكل إيزومر . أظهرت النتائ ج أ ن كلا الشكلي ن يتمتعا ن بخصائص مناسبة كعقاقير، مع امتصاص جيد عبر الجهاز الهضمي وانخفاض متوقع في السمية . وم ن الجدير بالذكر أ ن كلا من الإيزومري ن لم يُتوقع أ ن يعبر الحاجز الدموي الدماغي أو أ ن يكو ن ركيزة لبروتين P-gp. بشكل
Master's thesis in chemical engineering
Keywords: Resveratrol; Bovine Serum Albumin: الريسفيراترول، ألبومين مصل البقر، الالتحام الجزيئي، محاكاة الديناميكا الجزيئية، تحليل .ADMET